INSPIRASI RAGAM HIAS CANDI PLAOSAN DALAM KARYA BATIK TULIS SASTRA MENGGALA - Butsainah, Naadiah; Putri, Ramira Apriliani; Zahra, Nismara Aulia; Arifah, Leni Kurnia; nk, sugiyem (Jurusan Seni dan Desain, Fakultas Sastra, Universitas Negeri Malang, 2024)
Plaosan Temple is a relic of the Hindu Mataram Kingdom under the leadership of King Rakai Pikatan. The uniqueness of Plaosan Temple in addition to combining two religious elements is the many ornaments or reliefs found on the temple walls. These reliefs were explored and became the source of batik motif ideas in the Menggala Literature fashion collection. This study aims to create casual clothing with motif inspiration from the Plaosan temple and is done by writing batik using natural dyes and knowing respondents' opinions about the products made. The method used in this study is the research and development method (Research and Development) with the steps of Planning, Production, and Evaluation (PPE). Data collection techniques use observation, documentation, experiments, and questionnaires with a sample of 132 respondents. The results of the study were the creation of 4 casual clothes with 4 motif names, namely: Rona Menggala, Arca Menggala, Kicau Menggala, and Stupa Menggala. The clothes most liked by respondents were clothes with Rona Menggala motifs. While the results of the exploration of natural dyes secang wood and cinnamon with alum and quicklime fixation produce a brownish-orange color that resembles the color of terracotta.